Are Current Protein Recommendations for the Critically Ill Adequate for Patients on VV ECMO: Experience From a High‐Volume Center. Issue 2 (15th May 2019) - Pelekhaty, Stacy L.; Galvagno, Samuel M.; Lantry, James H.; Dolly, Katelyn N.; Herr, Daniel L.; Kon, Zachary N.; Deatrick, Kristopher B.; Cornachione, Christopher R.; Scalea, Thomas M.; Menaker, Jay
Abstract: Background: The nutrition needs of patients requiring extracorporeal membrane oxygenation (ECMO) have not been established in the literature. The purpose of this study is to investigate if current protein recommendations are adequate to achieve nitrogen equilibrium in patients on venovenous ECMO (VV ECMO). Methods: Patients aged ≥18 years on VV ECMO admitted November 2016 through January 2018 with a documented nitrogen balance (NB) study were included. Patients were stratified by body mass index (BMI) into obese (BMI ≥ 30 kg/m 2 ) and nonobese (BMI < 30 kg/m 2 ) categories for analysis. Results: After exclusions, 55 NB studies in 29 patients were analyzed. Twelve nonobese patients received a median of 2.1 g protein/kg actual body weight (ABW) (interquartile range [IQR]: 1.7–2.5), and median NB was −2.2 g/d (IQR: −7.4 to 2.8). In 17 obese patients, median protein delivery of 2 g protein/kg ideal body weight (IBW) (IQR: 1.7–2.5) achieved a median NB of −7.3 g/d (IQR: −12.6 to −2.8). Obese patients exhibited greater urinary urea nitrogen excretion than nonobese patients did (24.6 vs 17.6 g/d, P < 0.0001). Conclusions: Obese and nonobese patients undergoing VV ECMO may require more protein than is currently recommended for critical illness. Monitoring nutrition delivery and serial NB to assess prescription adequacy should be incorporated into routine patient care. Further research is needed to confirm these findings and create specific guidelines for patients on VV ECMO.